اضطراب الهذيان للشخصيّة الرئيسة في رواية عندما تكذب الحقيقة لآية رأفت (دراسة التحليل النفسي) - Ikhlasul Amalludin; Siti Amsariah (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This study aims to present the psychological disorder of delirium in the main character of the novel Indama Takzib al-Haqiqah by Ayaa Raafat, which is based on the abnormal behavior of the character, who cannot distinguish the truth of the surrounding reality. To uncover the delirium phenomenon, the researcher conducted a study using Freud's three levels of mind: the preconscious, the conscious, and the unconscious mind. This research uses qualitative descriptive research. The data collection technique used is careful and thorough reading of psychological phenomena and behavioral abnormalities that indicate the symptoms of delirium in the main character. This study found the following: 1. The form of psychological disturbance in the main character's delirium is in the form of imaginary images and actions based on his belief in the imaginary image that it is a real thing. 2. The influence of delirium causes the unconscious of the main character to dominate the consciousness, which manifests in the form of psychological disorders or abnormal psychological phenomena that he suffers